Rancangan Mesin Cuci Hemat Energi, Ekonomis dan Ramah Lingkungan dengan Memperhatikan Aspek Ergonomi - Kartika Suhada; Winda Halim; Kelvin Kelvin (Jurnal Rekayasa Sistem Industri, 2021)
Currently, the process of washing clothes is a commonly process that carried out in a household. To save human energy and washing time, a washing machine is used. There are a lot of washing machine models on the market, but in general the existing washing machine have standard functions, use electrical energy, quite expensive, and use materials that are less environmentally friendly. Based on these various shortcomings, it is necessary to design an innovative washing machine. The method used in this research is the concept of product design starting from seeing the needs to develop the desired product concept until making a product prototype. The washing machine designed in this study can be used to wash all types of clothes weighing 3 kilograms and is equipped with clothes drying device with a capacity of 20 clothes that rotates during the washing process, so it will speed up the drying process. In addition, the materials used come from secondhand goods, so the price is economic. This washing machine is not designed use electrical energy but kinetic energy, so it is environmentally friendly and can be also used as an exercise tool that can the user's body keep healthy and ergonomic when used.